Adat Rantau as a Solution for Multi-Ethnic Marriage in Pasaman, West Sumatera - Nofiardi, Nofiardi (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
Inter-ethnic marriages involving the Minangkabau and Mandailing people in the rantau region of Pasaman is increasingly unavoidable, even though people of the respective ethnicities keep preserving their customs. The issue about inter-ethnic marriage tradition in facilitating these two different regions between Minang and Mandailing in the rantau region is an interesting academic analysis. A comparison between it’s solutions with fiqh as well as the Compilation of Islamic Law (Kompilasi Hukum Islam) is also another issue that deserves a discussion. Therefore, the investigation of these issues applies a descriptive-qualitative research compiled through interviews with local figures and bundo kanduang and some sort of secondary sources. This article shows that adat rantau is a new alternative appeared as the solution raised from inter-ethnic marriages, especially between Minangkabau and Mandailing people. This emerging solution also opens up a pathway for the growth of bilateral or parental systems. This adat rantau is different from other regions in which inter-ethnic marriages occur, considering that some maintain the patrilineal system that resonates to fiqh and the Compilation of Islamic Law.